Miscibility of Poly(Methyl Methacrylate) and Poly(Vinylidene Fluoride) Examined by Thermally Stimulated Depolarization Current and Dielectric Relaxation Spectroscopy. Issue 4 (12th November 2020) - Korskanov, Valery; Fesenko, Olena
Abstract: Samples of poly(methyl methacrylate) (PMMA), poly(vinylidene fluoride) (PVDF) and melt blended PMMA/PVDF with weight ratios 4/1 and 3/2 were characterized by thermally stimulated depolarization currents (TSDC) in the temperature interval 123-303 K and by dielectric relaxation spectroscopy (DRS) in the frequency window 10 −2 − 106 Hz in the temperature interval 153-423 K. The TSDC thermograms and DRS profiles of the samples showed the two types of conducnivity – non-cooperative and cooperative. The experimental DRS data in the vicinity of the glass transition temperature, Tg, were quantitatively fitted to the Havriliak-Negami function and values of the maximum relaxation time were fitted to the Vogel-Tammann-Fulcher equation. Higher values of the strength index D, of the dielectric relaxation strength Δ ε and of the σ ac conductivity for the binary blends were considered as experimental evidence for nanoscale composition heterogeneities originating from strong specific interactions between the PMMA and PVDF. Therefore, we suggest the PMMA/PVDF blends will be usefull as effective materials for the manufacture of lithium-ion batteries, electrostatic capacitors with superior energy storage performance, polymer composite electrolytes for solar cells, etc.